Fluorination of silyl prosthetic groups by fluorine mediated silyl ether linker cleavage: a concept study with conditions applicable in radiofluorination - Carsten Sven Kramer; Luca Greiner; Klaus Kopka; Martin Schäfer (SpringerOpen, 2022)
Abstract Background Positron emission tomography (PET) is a powerful tool in medical imaging, especially in combination with the PET radionuclide fluorine-18 that possesses optimal characteristics. For labelling of biomolecules and low-molecular weight tracers, fluorine-18 can be covalently bound to silicon by either nucleophilic replacements of leaving groups (like ethers) or by isotope exchange of fluorine-19. While nucleophilic substitutions require additional purification steps for the removal of contaminants, isotope exchange with fluorine-18 results in low molar activity. Both challenges can be addressed with a detagging-fluorination of an immobilized silyl ether motif. Results By overcoming the susceptibility towards hydrolysis, optimized detagging conditions (improved reaction time, fluorination reagent, linker, and resin) could afford the highly sterically hindered silyl fluoride motifs, that are commonly applied in radiochemistry in small and semipreparative scales. The described reaction conditions with fluorine-19 are transferrable to conditions with [18F]fluoride and silyl fluorides were obtained after approx. 10 min reaction time and in high-purity after mechanical filtration. Conclusions We present a proof-of-concept study for a detagging-fluorination of two silyl ethers that are bound to an optimized amino alcohol resin. We show with our model substrate that our solid-phase linker combination is capable of yielding the desired silicon fluoride in amounts sufficient for biological studies in animals or humans under standard fluorination conditions that may also be transferred to a radiolabelling setting. In conclusion, our presented approach could optimize the molar activity and simplify the preparation of radiofluorinated silyl fluorides.